Culture of Reminiscence as a Part of Cultural Education - Jakubovská, Kristína; Jakubovská, Viera (Journal of Education Culture and Society, 2023)
Aim. The study explores the importance of culture of reminiscence with its identificational and integrational potential for the society and the ways that culture of reminiscence is applied within cultural institutions by means of cultural education. Methods. We used several scientific methods such as relational and content analysis, observation, induction and heuristics. Results. The research study summarises the role of cultural institutions within the culture of reminiscence and outlines various forms of reminiscence to be observed in cultural educational programmes. It explains the potential of cultural institutions and the roles they play within collective commemorating. It has interdisciplinary and applicational character and includes practical tips for cultural managers and cultural educators. Conclusion. Collective memory is an important condition for reproduction of culture and cultural identities. Individual memory is determined by social and cultural contexts (reference to Maurice Halbwachs´s social frames of memory). Cultural education naturally works with the notions of collective memory, traditions, identity and reminiscence. At the same time, it resembles a tool by means of which cultural identity, character and collective memory of individuals and social groups can be consciously shaped. Beside identificational context, there is also a prospective integrational and inclusive potential of cultural education. Several forms of reminiscence are applied within cultural education: reminiscence as reconstruction; reminiscence as (re)interpretation; reminiscence as creation; reminiscence as prevention and civic involvement; reminiscence as a tool of forming cultural identity; reminiscence as an expert reflection.